Aging and photodegradation of polycyclic aromatic compounds (PACs) emitted from biomass burning under sunlight and ultraviolet radiation - Ya-Jing Li; Zhen-Shan Huang; Yu-Ping Chen; Zhi-Hui Su; Yi-Huan Chen; Yuan Zeng; Yu-Qi Huang; Yu-Feng Guan; She-Jun Chen (Atmospheric Environment, 2026)

Intercomparison of gridded hydroclimate reconstruction datasets in Asia and evaluation of regional hydroclimate changes - Wenzheng Nie; Dunxian She; Jun Xia; Guizeng Qi (Journal of Hydrology, 2026)

Controlled regulation of endogenous enzymatic browning reshapes gel network formation and functional properties of edible insect Antheraea pernyi pupa protein - Yuyang She; Zihan Xiong; Jinghan Zhang; Xiaopei Hu; Xiaoliang Liu; Jun-Hua Shao (Food Research International, 2026)

Polyphenol oxidase mediated substrate selectivity underlies enzymatic browning in the edible insect Antheraea pernyi pupa - Yuyang She; Jinghan Zhang; Yanqun Liu; Jun-Hua Shao (Food Research International, 2026)

Synergistic engineering of oxygen vacancies and AuCu interface on ZnO for enhanced photocatalytic biomass valorization - Hao-Yu Chen; Wu-Dan Yang; Jie-Yang Dong; Ling-Bao Wu; Dan-Dan She; Ze-Kuan Zhang; Tian-Jun Gong; Qi Zhang; Yao Fu (Chemical Engineering Journal, 2026)

Precipitation and shortwave radiation dominate vegetation recovery times from flash droughts across Köppen–Geiger climate zones - Lei Zou; Wenzhe Zhu; Jun Xia; Feiyu Wang; Dunxian She; Chengjian Liu; Jiayuan Xu; Lingfeng Zuo (Agricultural and Forest Meteorology, 2026)

A nonlinear creep damage model for deep buried schist considering water content-stress-time coupling effects - Lei She; Xin-yang Hu; Li-feng Wen; Yan-long Li; Cheng-cheng Hu; Wen-jie Liu; Jun-tao Yan (Transportation Geotechnics, 2026)

Optimized Midbrain Organoid Transplantation Restores Dopaminergic Nigrostriatal Pathway and Motor Function in Parkinson’s Disease Mouse Model - Lin-Bo Chen; Xin-Yu She; Xi Jiang; Peng-Jian Wu; Chang-Qing Zheng; Jun Yao (Neuroscience Bulletin, 2026)

Redesigning explosive sensitization pathways via enzyme-catalyzed nitrite replacement for enhanced process safety and environmental performance - Kai-yan Lu; Quan Wang; Ying-jian Cao; Jun-Zhe Wang; Jian-she Xu; Ding-yu Feng; Jia-Bao Zhang; Zheng-jie Wang (Process Safety and Environmental Protection, 2026)

An integrated bipolar membrane electrodialysis process for sustainable detoxification and resource recovery of electrolytic manganese residue - Bo Ye; Weiqing She; Xubin Ma; Junye Huang; Jun Lan; Zenghui Diao (Journal of Environmental Management, 2026)

Tree-ring records reveal intensified early-summer hot–dry coupling in the Northeastern Tibetan Plateau - Wenzheng Nie; Jun Xia; Dunxian She; Kanon Kino; Taikan Oki (Global and Planetary Change, 2026)

Lower levels of oxygen content and carbon-to-nitrogen ratio in sludge drying off-gas balances simultaneous anammox and denitrification in a membrane biofilm reactor for synergistic bio-decontamination of trimethylamine and nitric oxide - Yuan Zeng; Xiu-Qin Tan; Lu-Lu Sun; Jia-Hua Wu; Han-Biao Yang; Zhen-Shan Huang; She-Jun Chen; Zai-Shan Wei (Bioresource Technology, 2026)

Response of hydrological drought to vegetation change in China - Xiaoyu Zhang; Dunxian She; Jun Xia; Zhihong Song; Tianyue Wang (Journal of Hydrology, 2026)

Identifying hotspots and impact factors of multi-type compound events over major global river basins - Lei Zou; Jiarui Yu; Gangsheng Wang; Feiyu Wang; Dunxian She; Jun Xia (Journal of Hydrology, 2026)

The influence of nonstationarity in hydro-meteorological variables on different drought types across the Chinese mainland - Xiaoyu Zhang; Dunxian She; Jun Xia (Science China Earth Sciences, 2026)

Enhanced Therapeutic Effects of Extracellular Vesicles Targeting MiR-137 Contribute to Functional Recovery by Attenuating Neuronal Injury After Ischemic Stroke - Hui-Xin Zhang; Li-Qing Tao; Yi-Hang Chen; Tian-Yi Jiang; Zhi-Yuan Ye; Wen She; Chang-Ying Chen; Ya-Li Han; Cui Qi; Chong Shen; Jun Gao (Neuroscience Bulletin, 2026)

Enhanced detoxification of electrolytic manganese residue via bioelectrosynthesized H2O2/OH– oxidation in a microbial electrolysis desalination and chemical-production cell - Xubin Ma; Weiqing She; Jun Lan; Manjun Yang; Xiangning Wei; Bo Ye (Journal of Environmental Chemical Engineering, 2026)

Hydrological droughts reduce carbon dioxide emission from the Yangtze River networks - Zhendan Wang; Dunxian She; Shaoda Liu; Xiaoyu Zhang; Zhihong Song; Jun Xia (Water Research, 2026)

Clostridium dalinum: A Novel Lactic Acid Bacterium with Excellent Antioxidant and Anti-inflammatory Functions Through NF-κB, Keap1-Nrf2-ARE Signaling Pathways - Zheng-Qiang Li; Rui Li; Wei Deng; Rui An; Ping Ma; Jun Li; Rong She; Xiao-Yan Yang; Xu Yang; Wen Xiao (Probiotics and Antimicrobial Proteins, 2026)

Biochar application enhances soil water storage in wet periods but intensifies drought conditions during dry periods in red soils - Yuanhang Fei; Zhipeng Liu; Jun Yi; Dongli She; Weiwen Qiu; Lan Jiang; Muxing Liu; Shenglong Li; Hanjiang Nie; Qi Li; Xin Ni; Hailin Zhang (Soil and Tillage Research, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

Wenzhouxiangella psychrophila sp. nov., Wenzhouxiangella indolica sp. nov., and Halotectona sediminis gen. nov., sp.nov., three novel taxa with ability of IAA production from saline lake sediment - Qing-Yu Xu; Tayyiba Habib; Lei Gao; Dildar Wu; Xin-Yao Li; Thi-Nhan Khieu; Yue-Heng Chen; Yao Zhang; Yong-Hong Liu; Ting-Ting She; Bao-Zhu Fang; Wen-Jun Li (Systematic and Applied Microbiology, 2026)

Precipitation deficit related drought induces the decrease in the sensitivity of GPP to air temperature and radiation in mainland China - Yiheng Wei; Dunxian She; Hui Zheng; Xuejun Zhang; Lvlv Wang; Jun Xia (Journal of Hydrology, 2026)

Amino-functionalized covalent organic framework-carboxylated carbon nanotubes via covalent bonding for sensitive Tau electrochemical immunosensing - Ping He; Wen-Tao Li; A-Min Zhu; Si-Yuan An; Jun-Ping Ma; She-Ying Dong; Yuan-Zhen Zhou; Jun-Jie Zhu (Chemical Engineering Journal, 2026)

A modified PML model considering anthropogenic heat to estimate urban evapotranspiration - Xinrong Shi; Dunxian She; Jun Xia; Yongyong Zhang; Ronglin Tang; Dongdong Kong (Urban Climate, 2025)

Polyphenol oxidase from edible insect Antheraea pernyi pupa: Characterization and browning mechanism - Yuyang She; Shuyi Song; Yanqun Liu; Yanwei Zhang; Jun-Hua Shao (Food Chemistry, 2025)

Platinum-group element geochemistry of the Heigutian FeTi oxide-bearing layered intrusion, Emeishan large igneous province, SW China - Yu-Wei She; Lie-Meng Chen; Song-Yue Yu; Jun-Nian Yi; Hai-Long He (Lithos, 2025)

Leveraging emergent constraints to reduce uncertainty in future compound drought and heatwave events across mainland China - Mengyu Wu; Dunxian She; Qin Zhang; Yao Yue; Jun Xia; Wenting Hu; Yuliang Zhou (Journal of Hydrology, 2025)

Crystal-scale heterogeneity of Sn isotopes in Cassiterite: implications for reconstructing ore-forming processes in magmatic-hydrothermal systems - Liang Han; Guo-Guang Wang; Pei Ni; Jun-Yi Pan; Jia-Xin She; Wei Tan; Weiqiang Li (Geochimica et Cosmochimica Acta, 2025)

Volatile organic compounds in various workplaces and during commutes in a Chinese city: occurrence and health risks for different occupations - Jin-Long Mai; Yi Yang; Yuan Zeng; Song Liu; Zhen-Shan Huang; Jia-Hua Wu; Ya-Jing Li; She-Jun Chen (Environmental Research, 2025)

Z-scheme heterojunction engineered covalent organic polymer for thermodynamically optimized CO2 photoreduction - Jiaxin Rong; Xuejing Li; Qiang Xu; Jingwei Han; Jing Zhang; Ke Ren; Ping She; Jun-Sheng Qin; Heng Rao (Chemical Engineering Journal, 2025)

Increasing impacts of compound extreme droughts on vegetation productivity in China - Guizeng Qi; Jinxi Song; Shouzhi Chen; Yufeng Gong; Hongying Bai; Dunxian She; Jun Xia; Yongshuo H. Fu (Journal of Hydrology, 2025)

Synergistic microaerobic bio-decontamination of dimethyl sulfide and elemental mercury in the low-O2 content flue gas by a sulfur-oxidizing membrane biofilm reactor - Han-Biao Yang; Lu-Lu Sun; Xiu-Qin Tan; Yuan Zeng; Yu-Qi Huang; Zhen-Shan Huang; She-Jun Chen; Zai-Shan Wei (Chemical Engineering Journal, 2025)

Five-Century monthly streamflow reconstruction of the upper Brahmaputra River reveals Historically frequent and intense Drought-Flood abrupt alternation events - Wenzheng Nie; Dunxian She; Jun Xia (Journal of Hydrology, 2025)

Direct and indirect effects of spring phenology on forest transpiration - Lvlv Wang; Dunxian She; Yuting Yang; Lin Meng; Jun Xia (Agricultural and Forest Meteorology, 2025)

Chemical constituents from the flowers of Inula japonica: Chemotaxonomic significance and antidiabetic activity - Jun-Li Cheng; Chang Yan; Hong-Fang Cai; Kai-Wen Kang; Dong-Li Li; Hong-Guang Li; Li-She Gan (Biochemical Systematics and Ecology, 2025)

Applicability of Copernicus marine service products for the eutrophication status assessment of the Baltic Sea - Oliver Samlas; Stella-Theresa Luik; Vasily Korabel; Jun She; Urmas Lips (Marine Pollution Bulletin, 2025)

Stabilization effects and mechanisms of lignin-based hydrogel-coated sulfide nano-zero-valent iron on lead and cadmium contamination in soil - Qianqian Ma; Wangwang Xu; Jun Xia; Qing Zhen; Diao She (Journal of Hazardous Materials, 2025)

Electrocatalytic upcycling of polylactic acid hydrolysate and simultaneous hydrogen production - Ping He; Jiang-nan Xu; Jia-yang Dou; Bing Xu; She-ying Dong; Ting-lin Huang; Jun-Jie Zhu (Chemical Engineering Journal, 2025)

Facilitated charge transfer of stable multivariate transition Metal-organic frameworks for photocatalytic CO2 reduction - Jiahui Wu; Zhaoguo Xu; Hai Sun; Heng Rao; Ping She; Jun-sheng Qin (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Impact on nonlinear runoff of LID facilities and parameter response in the TVGM model - Pengjun Li; Luwen Zhuang; Kairong Lin; Dunxian She; Qiang Wang; Wei Luo; Jianliang He; Jun Xia (Journal of Hydrology, 2025)

Trujillonella humicola sp. nov., a siderophore-synthesizing bacterium isolated from black soil in Northeast China - Ying Wang; Le-Bin Chen; Yu-Ting OuYang; Jia-Ying Xing; Ke Zhang; Nan-Feng Chen; Ting-Ting She; Shuang Wang; Jian-Yu Jiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Multi-scale analysis of six evapotranspiration products across China: Accuracy, uncertainty and spatiotemporal pattern - Lingfeng Zuo; Lei Zou; Jun Xia; Liping Zhang; Hui Cao; Dunxian She (Journal of Hydrology, 2025)

Piezoelectric-photothermal catalytic degradation of BPA by Cs0.32WO3 nanorods in dark-full spectrum - Chunyan Zeng; Guoqiang Tan; Bixin Zhang; Linxin Guo; Xiongtao Wu; Sizhe Fan; Wenlong Liu; Min Wang; Ao Xia; Huijun Ren; Liaona She; Yaxiong Yang; et al. (Journal of Environmental Chemical Engineering, 2025)

Boosting anode interfacial stability in All-Solid-State lithium hybrid batteries with MCMB-Modified stainless steel current collector - Abebe Taye Fenta; Yosef Nikodimos; Semaw Kebede Merso; Ayenew Meniber; Misganaw Adigo Weret; Kassie Nigus Shitaw; Bereket Woldegbreal Taklu; Felika Valencia; Tsung-I Yeh; Chia Lung Hsieh; Chia-Yu Chang; Ya-Jun Liu; et al. (Chemical Engineering Journal, 2025)

Uncertainty analysis of global meteorological drought in CMIP6 projections - Qing Niu; Dunxian She; Jun Xia; Qin Zhang; Yu Zhang; Tianyue Wang (Climatic Change, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

In situ construction of cobalt phthalocyanine covalent organic polymer on mesoporous graphitic carbon nitride for boosting photocatalytic CO2 reduction - Jiaxin Rong; Qiang Xu; Jingwei Han; Ke Ren; Jing Zhang; Xue Zhao; Ping She; Jun-Sheng Qin; Heng Rao (Chemical Engineering Journal, 2025)

On-demand coastal modelling with two-way nesting - Vilnis Frishfelds; Jun She; Jens Murawski (Ocean Dynamics, 2025)

New perspectives on urban stormwater management in China, with a focus on extreme rainfall events - Pengjun Li; Luwen Zhuang; Kairong Lin; Dunxian She; Qiuling Chen; Qiang Wang; Jun Xia (Natural Hazards, 2025)

Lithospheric structure beneath Tibet based on gravity data from World Gravity Map 2012 - Jun Li; Jinxi Li; Weilin Li; Zhengwei Xu; Aidong She (Journal of Asian Earth Sciences, 2025)

Preservation of biosignatures in Neoproterozoic phosphorites metamorphosed at temperatures >450 °C - Kenan Cao; Zhenbing She; Dominic Papineau; Jingbo Nan; Chao Chen; Reza Deevsalar; Ayetullah Tunc; Qunfeng Xiao; Kang-Jun Huang; Yuanming Pan (Chemical Geology, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Parafrigoribacterium soli sp. nov. and Parafrigoribacterium humi sp. nov., two novel siderophore-synthesizing species isolated from black soil - Yu-Ting OuYang; Le-Bin Chen; Jian-Yu Jiao; Zi-Xuan Hu; Jiong-Shan Wang; Tian-Hang Yang; Jun Xiao; Ting-Ting She; Pin-Jiao Jin; Shuang Wang; Lan Liu; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Optimizing soil remediation with multi-functional L-PH hydrogel: Enhancing water retention and heavy metal stabilization in farmland soil - Qianqian Ma; Jun Xia; Wangwang Xu; Dana Hashan; Qing Zhen; Diao She (Science of The Total Environment, 2025)

Aquibaculum sediminis sp. nov., a halotolerant bacteria isolated from salt lake sediment - Qing-Yu Xu; Lei Gao; Dildar Wu; Xin-Yao Li; Yong-Hong Liu; Yao Zhang; Yue-Heng Chen; Ting-Ting She; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Revealing the key antioxidant compounds and potential action mechanisms of Chinese Cabernet Sauvignon red wines by integrating UHPLC-QTOF-MS-based untargeted metabolomics, network pharmacology and molecular docking approaches - Zhi-Xin Peng; Hui-Wen Gu; Yuan Pan; Yan Wang; Jun Yan; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Impacts of urbanization on urban-rural VPD disparities across different subregions in China: A quantitative analysis based on station-pairing and partial differential methods - Siqi Gong; Dunxian She; Jun Xia; Tianyue Wang (Atmospheric Research, 2024)

Pedobacter deserti sp. nov., a novel species isolated from desert soil - Jie Huang; Shuai Li; Ting-Ting She; Jun Liu; Yi-Jun Mo; Wen-Hui Lian; Dong-Ya Zhang; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

A predictive fuzzy logic and rule-based control approach for practical real-time operation of urban stormwater storage system - Lanxin Sun; Jun Xia; Dunxian She; Wenlu Ding; Jialiang Jiang; Biao Liu; Fang Zhao (Water Research, 2024)

Confinement of Z-scheme organic-inorganic heterojunction into mesoporous zeolite for efficient photocatalytic solar fuel generation - Mai-Yan Nan; Heng Rao; Ping She; Jun-Sheng Qin (Chemical Engineering Journal, 2024)

Regulated charge transfer by cascade dual Z-scheme heterojunction of HCdS@ZnIn2S4-Cobalt porphyrin for efficient photocatalytic solar fuel production - Tengfei Bao; Chenxi Tang; Shuming Li; Ping She; Heng Rao; Jun-sheng Qin (Chemical Engineering Journal, 2024)

Self-standing Z-scheme structured heterogeneous nanosheet arrays of ZnIn2S4/cobalt porphyrin sulfonate for bifunctional photocatalytic carbon dioxide reduction and antibacterial - Shuming Li; Xuejing Li; Heng Rao; Ping She; Weng-Chon Max Cheong; Jun-Sheng Qin (Chemical Engineering Journal, 2024)

Soil moisture and precipitation dominate the response and recovery times of ecosystems from different types of flash drought in the Yangtze River Basin - Chen Hu; Dunxian She; Gangsheng Wang; Liping Zhang; Zhaoxia Jing; Si Hong; Zhihong Song; Jun Xia (Agricultural and Forest Meteorology, 2024)

Pollution loads in the middle-lower Yangtze river by coupling water quality models with machine learning - Sheng Huang; Jun Xia; Yueling Wang; Gangsheng Wang; Dunxian She; Jiarui Lei (Water Research, 2024)

Mechanistic insights into tris(2-chloroisopropyl) phosphate biomineralization coupled with lead (II) biostabilization driven by denitrifying bacteria - Zhen-Shan Huang; Xiu-Qin Tan; Han-Biao Yang; Yuan Zeng; She-Jun Chen; Zai-Shan Wei; Yu-Qi Huang (Science of The Total Environment, 2024)

Insights into the variations of polycyclic aromatic hydrocarbons and their nitrated and oxygenated derivatives in urban airborne PM2.5 - Yi-Huan Chen; Yuan Zeng; Zhen-Shan Huang; Wen-Qing Mo; Yu-Qi Huang; Tao Wang; She-Jun Chen (Atmospheric Environment, 2024)

Exosomes from Hypoxia-treated Mesenchymal Stem Cells: Promoting Neuroprotection in Ischemic Stroke Through miR-214-3p/PTEN Mechanism - Qian Wu; Jia-Huan Wu; Zhi-Yuan Ye; Wen She; Wen-Jie Peng; Hui-Xin Zhang; Cui Qi; Tian Tian; Xiao-Yu Hou; Jun Gao (Molecular Neurobiology, 2024)

Rufibacter psychrotolerans sp. nov., a Cold-Tolerating Novel Species Isolated from Desert Soil - Jun Liu; Shuai Li; Ting-Ting She; Jie Huang; Wen-Hui Lian; Yi-Jun Mo; Dong-Ya Zhang; Lei Dong; Wen-Jun Li (Current Microbiology, 2024)

Unlocking Zn biofortification: leveraging high-Zn wheat and rhizospheric microbiome interactions in high-pH soils - Jun Yang; Chenrui Liu; Runze Wang; Junfeng Xu; Cui Huang; Wenxiang Wang; Siqi Zhang; Wenting She; Xuemei Zhang; Mei Shi; Eduardo Moreno-Jiménez; Yinglong Chen; et al. (Biology and Fertility of Soils, 2024)

Spatial variation, emissions, transport, and risk assessment of organophosphate esters in two large petrochemical complexes in southern China - Wen-Qing Mo; Zhen-Shan Huang; Qi-Qi Li; Jun Yao; Chun-You Zhu; Hui-Ying Guo; Yuan Zeng; She-Jun Chen (Journal of Environmental Management, 2024)

Tin isotope heterogeneity and baseline of the upper continental crust - Jia-Xin She; Weiqiang Li; Edith Kubik; Frédéric Moynier; Xiang-Long Luo; Jun Mu; Shichao An; Chang-Zhi Wu; Zhongya Hu; Junfeng Ji (Geochimica et Cosmochimica Acta, 2024)

Local microenvironment modulation of zirconium-porphyrinic frameworks for CO2 reduction - Xue Zhao; Chang-Yan Zhu; Heng Rao; Dong-Ying Du; Min Zhang; Ping She; Li Li; Jun-Sheng Qin (Chemical Engineering Journal, 2024)

Cross-Scale Prediction Model of Oxygen Diffusion in Concrete Under Dry Conditions - Chuanye Su; Jun Xu; Wei She; Chuanqing Fu (Transport in Porous Media, 2024)

Effect of using reclaimed water via furrow and subsurface drip systems under alternate partial root-zone irrigation mechanism on crops growth and soil properties - Mahmoud S. Hashem; Wei Guo; Xue-Bin Qi; Ping Li; Ying-jun She; Jiaxin Cui; Tong Li (Irrigation Science, 2024)
The growing population in the face of water scarcity inevitably necessitates the quest for alternative sources of irrigation water, which integrates them with irrigation strategies for improved agricultural productivity to meet the Sustainable Development Goals. A three-year field experiment was conducted in 2017, 2018, and 2019 to investigate the effect of water quality (reclaimed water (RW) and clean water (CW)), irrigation techniques (subsurface drip irrigation (SDI) and furrow irrigation (FUI)), irrigation methods (full irrigation (FI) and alternate partial root-zone irrigation (APRI) (70% ETc)), and their interactions on the fresh fruit yield (FY), irrigation water use efficiency (IWUE), and nitrogen use efficiency (NUE) of tomatoes. Further, electrical conductivity (EC), pH, and organic matter (OM) of soil were evaluated. The experiments were undertaken over three growing spring seasons in a greenhouse at the Chinese Academy of Agricultural Sciences in Henan Province, China. Throughout the three years of this study, the yield, the IWUE, and the NUE values of all treatments under RW were higher than those corresponding values under CW. The trend was the same under SDI as it was under FUI. Statistical analyses revealed that there was no significant effect ( P > 0.05) of water quality, irrigation technique, and irrigation methods on the soil EC, pH, and OM over the three years. In addition, the interaction between the different experimental factors over the three years of the study was not significant. In conclusion, the application of RW under SDI can result in saving CW and increasing productivity without any negative effect on the investigated soil properties. Furthermore, when RW-SDI is used in conjunction with APRI, it can result in increasing IWUE.

Soil moisture plays an increasingly important role in constraining vegetation productivity in China over the past two decades - Guizeng Qi; Dunxian She; Jun Xia; Jinxi Song; Wenzhe Jiao; Jiayu Li; Zheqiong Liu (Agricultural and Forest Meteorology, 2024)

Biodegradable magnesium-based alloy skull repairment (MASR) for skull bone defect: In vitro and in vivo evaluation - Anke Zhang; Xiaoyu Wang; Zeyu Zhang; Xiyue Zhang; Junjie Wang; Yibo Liu; Yan Chen; Jiarui Chen; Ting Chen; Yongjie Wang; Jun Yu; Jia She; et al. (Chemical Engineering Journal, 2024)

Exploring dissolved N2O characteristics and unearthing indirect N2O emission factors in the shallow groundwater of paddy and upland fields - Yongchun Pan; Dongli She; Jihui Ding; Zhenqi Shi; Alimu Abulaiti; Lei Hu; Xuan Huang; Ruliang Liu; Fang Wang; Jun Shan; Yongqiu Xia (Science of The Total Environment, 2024)

Evaluation of the number of events’ influence on model performance and uncertainty in urban data-scarce areas based on behavioral parameter ranking method - Yingying Wu; Dunxian She; Jun Xia; Yongyong Zhang; Lei Zou (Journal of Hydrology, 2024)

Coping with groundwater pollution in high-nitrate leaching areas: The efficacy of denitrification - Yongchun Pan; Dongli She; Jihui Ding; Alimu Abulaiti; Junhan Zhao; Ying Wang; Ruliang Liu; Fang Wang; Jun Shan; Yongqiu Xia (Environmental Research, 2024)

Spatiotemporal variations, sources, and atmospheric transformation potential of volatile organic compounds in an industrial zone based on high-resolution measurements in three plants - Jin-Long Mai; Xing-Cong Cai; De-Yao Luo; Yuan Zeng; Yu-Feng Guan; Wei Gao; She-Jun Chen (Science of The Total Environment, 2024)

Climate change dominates the increasing exposure of global population to compound heatwave and humidity extremes in the future - Yiheng Wei; Dunxian She; Jun Xia; Gangsheng Wang; Qin Zhang; Shengzhi Huang; Yu Zhang; Tianyue Wang (Climate Dynamics, 2024)

The intercomparison of six 0.1°×0.1° spatial resolution evapotranspiration products across mainland China - Xinrong Shi; Dunxian She; Jun Xia; Renli Liu; Tianyue Wang (Journal of Hydrology, 2024)

Risk assessment of airborne agricultural pesticide exposure in humans in rural China - Yuzhao Hu; Shuai Wu; Changcai Wu; Zhimin Wei; Jun Ning; Dongmei She (Environmental Geochemistry and Health, 2024)

Drainage ditches are significant sources of indirect N2O emissions regulated by available carbon to nitrogen substrates in salt-affected farmlands - Alimu Abulaiti; Dongli She; Yongchun Pan; Zhenqi Shi; Lei Hu; Xuan Huang; Jun Shan; Yongqiu Xia (Water Research, 2024)

Ditch level-dependent N removal capacity of denitrification and anammox in the drainage system of the Ningxia Yellow River irrigation district - Zhenqi Shi; Dongli She; Yongchun Pan; Alimu Abulaiti; Yihua Huang; Ruliang Liu; Fang Wang; Yongqiu Xia; Jun Shan (Science of The Total Environment, 2024)

Urban water system theory and its model development and application - Jun Xia; Yongyong Zhang; Dunxian She; Shiyan Zhang; Jun Yang; Mingquan Lv; Xiang Zhang; Anqi Luo; Shengjun Wu; Yang Liu (Science China Earth Sciences, 2024)

Rapid nanomolar detection of Δ9-tetrahydrocannabinol in biofluids via electrochemical aptamer-based biosensor - Yu Xie; Jin-Ping She; Jia-Xing Zheng; Kalle Salminen; Jian-Jun Sun (Analytica Chimica Acta, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Extreme Sn isotope fractionation in highly evolved granites - Ke-Ke Sun; Jia-Xin She; De-Hong Du; Weiqiang Li; Jun Deng (Chemical Geology, 2024)

Variations in lunar regolith properties with depth as revealed by Chang'e-5 samples - Siyuan Zhao; Long Xiao; Yuqi Qian; Jiawei Zhao; Zhenbing She; Qi He; Zaicong Wang; Xinyi Wang; Kenan Cao; Xiangbin Zeng; Yixuan Wang; Jiahuai Sun; et al. (Icarus, 2023)

Unraveling the genomic diversity and ecological potential of the genus Demequina: insights from comparative analysis of different saline niche strains - Lei Gao; Bao-Zhu Fang; Chun-Yan Lu; Kun-Hui Hong; Xin-Yu Huang; Ting-Ting She; Min Xiao; Wen-Jun Li (Frontiers in Marine Science, 2023)
During an investigation of the culturable microbial diversity of sediments with salinity from tidal flats and saline lake, seven strains of the genus Demequina were harvested. The genomic analysis and physiological characteristics of strains of this genus have unveiled their significant potential in degrading complex carbon source such as lignin, hemicellulose, chitin, and oligosaccharides. In addition, these strains show potential abilities in nitrite ammonification and sulfide oxidation. These findings not only improved our understanding of their metabolic model, but also provided valuable insights into their ecological roles. Four new species of the genus Demequina are described: Demequina litoralis sp. nov., with SYSU T00192 T designated as the type species; Demequina zhanjiangensis sp. nov., with SYSU T00b26 T as the type species; Demequina lignilytica sp. nov., with SYSU T00068 T as the type species; and Demequina muriae sp. nov., with EGI L300058 T as the type species. Additionally, strains SYSU T0a273, SYSU T00039-1, and SYSU T00039 are identified as different strains of Demequina lignilytica . Our study thus sheds light on the diversity, biological significance, and ecological contribution of the Demequina genus in different habitats.

Research on L1 Adaptive Control of Autonomous Underwater Vehicles with X-Rudder - Jianping Yuan; Yingying She; Yinghao Zhang; Jun Xu; Lei Wan (Journal of Marine Science and Engineering, 2023)
This study focuses on addressing the the coupling problem of the vertical and horizontal plane of an autonomous underwater vehicle (AUV) with an X-rudder. To guarantee the steering performance of the AUV, a depth and course control algorithm based on an L1 adaptive control algorithm (L1AC) is proposed. Firstly, the linear quadratic regulator (LQR) is designed on the basis of an AUV vertical and horizontal linear model, and the system has optimal control quality for both of the nominal vertical and horizontal models. Secondly, the nonlinear state predictor, disturbance estimator, and adaptive controller are designed separately, which is used for the compensation of the uncertainty and disturbance of the AUV dynamic. Finally, the rudder angle allocation algorithm is designed to realize the rudder angle command of the cross rudder to the X-rudder. The simulation and experiment results show that the adaptive control algorithm proposed in this paper can effectively control AUV to complete high-performance course and depth control. Based on the experiments, the prospects and shortcomings of the L1AC, LQR and MRAC algorithm in AUV control are compared and analyzed.

Fit-for-Purpose Information for Offshore Wind Farming Applications—Part-II: Gap Analysis and Recommendations - Johannes Schulz-Stellenfleth; Anouk Blauw; Lauri Laakso; Baptiste Mourre; Jun She; Henning Wehde (Journal of Marine Science and Engineering, 2023)
Offshore wind energy installations in coastal areas have grown massively over the last decade. This development comes with a large number of technological, environmental, economic, and scientific challenges, which need to be addressed to make the use of offshore wind energy sustainable. One important component in these optimization activities is suitable information from observations and numerical models. The purpose of this study is to analyze the gaps that exist in the present monitoring systems and their respective integration with models. This paper is the second part of two manuscripts and uses results from the first part about the requirements for different application fields. The present solutions to provide measurements for the required information products are described for several European countries with growing offshore wind operations. The gaps are then identified and discussed in different contexts, like technology evolution, trans-European monitoring and modeling initiatives, legal aspects, and cooperation between industry and science. The monitoring gaps are further quantified in terms of missing observed quantities, spatial coverage, accuracy, and continuity. Strategies to fill the gaps are discussed, and respective recommendations are provided. The study shows that there are significant information deficiencies that need to be addressed to ensure the economical and environmentally friendly growth of the offshore wind farm sector. It was also found that many of these gaps are related to insufficient information about connectivities, e.g., concerning the interactions of wind farms from different countries or the coupling between physical and biological processes.

Isoptericola croceus sp. nov., a novel actinobacterium isolated from saline–alkali soil - Yu-Ting OuYang; Ai-Ping Lv; Lan Liu; Ting-Ting Li; Yi Zhou; Ting-Ting She; Li-Xiang Cao; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2023)

Fit-for-Purpose Information for Offshore Wind Farming Applications—Part-I: Identification of Needs and Solutions - Jun She; Anouk Blauw; Lauri Laakso; Baptiste Mourre; Johannes Schulz-Stellenfleth; Henning Wehde (Journal of Marine Science and Engineering, 2023)
The rapid expansion of offshore wind farms (OWFs) in European seas is accompanied by many challenges, including efficient and safe operation and maintenance, environmental protection, and biodiversity conservation. Effective decision-making for industry and environmental agencies relies on timely, multi-disciplinary marine data to assess the current state and predict the future state of the marine system. Due to high connectivity in space (land–estuarial–coastal sea), socioeconomic (multi-sectoral and cross-board), and environmental and ecological processes in sea areas containing OWFs, marine observations should be fit for purpose in relation to multiple OWF applications. This study represents an effort to map the major observation requirements (Part-I), identify observation gaps, and recommend solutions to fill those gaps (Part-II) in order to address multi-dimension challenges for the OWF industry. In Part-I, six targeted areas are selected, including OWF operation and maintenance, protection of submarine cables, wake and lee effects, transport and security, contamination, and ecological impact assessments. For each application area, key information products are identified, and integrated modeling–monitoring solutions for generating the information products are proposed based on current state-of-the-art methods. The observation requirements for these solutions, in terms of variables and spatial and temporal sampling needs, are therefore identified.

EuroGOOS roadmap for operational coastal downstream services - Ghada El Serafy; Lőrinc Mészáros; Vicente Fernández; Arthur Capet; Jun She; Marcos Garcia Sotillo; Angelique Melet; Sebastien Legrand; Baptiste Mourre; Francisco Campuzano; Ivan Federico; Antonio Guarnieri; et al. (Frontiers in Marine Science, 2023)
The EuroGOOS Coastal working group examines the entire coastal value chain from coastal observations to services for coastal users. The main objective of the working group is to review the status quo, identify gaps and future steps needed to secure and improve the sustainability of the European coastal service provision. Within this framework, our white paper defines a EuroGOOS roadmap for sustained “community coastal downstream service” provision, provided by a broad EuroGOOS community with focus on the national and local scale services. After defining the coastal services in this context, we describe the main components of coastal service provision and explore community benefits and requirements through sectoral examples (aquaculture, coastal tourism, renewable energy, port, cross-sectoral) together with the main challenges and barriers to user uptake. Technology integration challenges are outlined with respect to multiparameter observations, multi-platform observations, the land-coast-ocean continuum, and multidisciplinary data integration. Finally, the technological, financial, and institutional sustainability of coastal observing and coastal service provision are discussed. The paper gives special attention to the delineation of upstream and downstream services, public-private partnerships and the important role of Copernicus in better covering the coastal zone. Therefore, our white paper is a policy and practice review providing a comprehensive overview, in-depth discussion and actionable recommendations (according to key short-term or medium-term priorities) on the envisaged elements of a roadmap for sustained coastal service provision. EuroGOOS, as an entity that unites European national operational oceanography centres, research institutes and scientists across various domains within the broader field of operational oceanography, offers to be the engine and intermediary for the knowledge transfer and communication of experiences, best practices and information, not only amongst its members, but also amongst the different (research) infrastructures, institutes and agencies that have interests in coastal oceanography in Europe.

The changing characteristics of propagation time from meteorological drought to hydrological drought in the Yangtze River basin, China - Xiaoyu Zhang; Dunxian She; Jun Xia; Liping Zhang; Cuiling Deng; Zheqiong Liu (Atmospheric Research, 2023)

Editorial: Cleaning litter by developing and applying innovative methods in European seas - George Triantafyllou; George Triantaphyllidis; Annika Pollani; Jun She; Joydeep Dutta; Michael St. John; Marco Faimali; Roy Brouwer; Pavel Stoev (Frontiers in Marine Science, 2023)

Precisely modulate interfacial Bi-O bridge bond in Co-TCPP/Bi3O4Br to trigger long-lasting charge separation for boosting CO2 photoreduction - Yi Zhang; Fangyu Guo; Keke Wang; Jun Di; Bokki Min; Huiyuan Zhu; Hailong Chen; Yu-Xiang Weng; Jiayu Dai; Yuanbin She; Jiexiang Xia; Huaming Li (Chemical Engineering Journal, 2023)

Integrated intra-storm predictive analysis and real-time control for urban stormwater storage to reduce flooding risk in cities - Lanxin Sun; Jun Xia; Dunxian She; Qizhong Guo; Yuming Su; Wenyucheng Wang (Sustainable Cities and Society, 2023)

Climate change rather than vegetation greening dominates runoff change in China - Zhihong Song; Jun Xia; Gangsheng Wang; Dunxian She; Chen Hu; Shilong Piao (Journal of Hydrology, 2023)

Calpain-TRPC6 signaling pathway contributes to propofol-induced developmental neurotoxicity in rats - Ying-Jun She; Hai-Ping Xu; Yin Gao; Qiong Wang; Jun Zheng; Xiangcai Ruan (NeuroToxicology, 2023)

Revegetation affects the response of land surface phenology to climate in Loess Plateau, China - Lvlv Wang; Dunxian She; Jun Xia; Lin Meng; Lingcheng Li (Science of The Total Environment, 2023)

The quantitative assessment of impact of pumping capacity and LID on urban flood susceptibility based on machine learning - Yingying Wu; Dunxian She; Jun Xia; Jiyun Song; Tong Xiao; Yan Zhou (Journal of Hydrology, 2023)

Long-term environmental risks of the Baltic Sea's "memory effect" revealed by ocean modeling and observation of reprocessing-derived radiotracers - Mu Lin; Jun She; Jens Murawski; Xiaolin Hou; Jixin Qiao (Journal of Hazardous Materials, 2023)

Ketamine modulates neural stem cell differentiation by regulating TRPC3 expression through the GSK3β/β-catenin pathway - Ying-Jun She; Junping Pan; Liang-Ming Peng; Li Ma; Xinying Guo; Dong-Xu Lei; Huai-Zhen Wang (NeuroToxicology, 2023)

Multidimensional analysis of the essential elements in pregnant women's whole blood and characterization of maternal status by elemental pattern - Min Zhan; Wenbin Chen; Zhichao Wang; Xuhui She; Qiaoxuan Zhang; Heng Dong; Jun Yan; Zhuoyang Li; Liqiao Han; Haibiao Lin; Xianzhang Huang; Beibei Zhao (Journal of Trace Elements in Medicine and Biology, 2023)

A hybrid time- and signature-domain Bayesian inference framework for calibration of hydrological models: a case study in the Ren River basin in China - Song Liu; Dunxian She; Liping Zhang; Jun Xia (Stochastic Environmental Research and Risk Assessment, 2023)

Developing Realistic Models for Assessing Marine Plastic Pollution in Semi-Enclosed Seas - Jun She; Asbjørn Christensen; Francesca Garaventa; Urmas Lips; Jens Murawski; Manolis Ntoumas; Kostas Tsiaras (Oceanography, 2023)
Having steadily increased with global production in the past 50 years, the presence and accumulation of plastic debris is now recognized as a major environmental problem, with consequences directly affecting not only marine ecosystems, but also society and human well-being. After human activities release plastic litter, it is either directly discharged into the ocean or it is transported to the sea via inland pathways (e.g., rivers, lakes, wastewater treatment plants). Once in the ocean, plastics are further transported and transformed by processes such as ocean currents, winds and waves, water dispersion, fragmentation, biofouling, sinking, sedimentation, and beaching (Figure 1).

Comparative transcriptome analyses identify genes involved into the biosynthesis of forsythin and forsythoside A in Forsythia suspensa - Wang Jun Yuan; Su Ping Zhang; Zhi Yin He; Yan Xia He; She Qi He; Li Jun Liu; Xin Sun; Qin Li (Functional & Integrative Genomics, 2022)

Modeling impacts of mining activity-induced landscape change on local climate - Hongru Bi; Wei Chen; Jun Li; Junting Guo; Changchao She (Environmental Science and Pollution Research, 2022)

Modeling drift and fate of microplastics in the Baltic Sea - Jens Murawski; Jun She; Vilnis Frishfelds (Frontiers in Marine Science, 2022)
Marine plastic litter has been recognized as a growing problem and a threat to the marine environment and ecosystems, although its impacts on the marine life are still largely unknown. Marine protection and conservation actions require a detailed knowledge of the marine pathways, sources, and sinks of land-emitted plastic pollution. Model-based assessments provide a systematic way to map the occurrence of microplastics in the marine environment and to link the coastal sources to the accumulation zones in the sea. New modeling capacities have been developed, which include relevant key processes, i.e., current- and wave-induced horizontal and vertical transport, biofilm growth on the particle surface, sinking, and sedimentation. The core engine is the HIROMB-BOOS ocean circulation model, which has been set up for the Baltic Sea in a high, eddy-permitting resolution of approximately 900 m. We introduce the three-dimensional modeling tool for microplastics and demonstrate its ability to reproduce the drift pattern of microplastics in the Baltic Sea. The results of a multiyear run 2014–2019 provide the basis for an extensive validation study, which allows the evaluation of the model quality. The assessments focus on three types of microplastics, from car tires and household products, with different densities and particle sizes, which cover a broad range of land-emitted microplastic pollution. We show that the model is applicable to the task of identifying high concentration zones in the Baltic Sea and that it can be a useful tool to support the study of the environmental impacts of microplastics in the Baltic Sea. Our results suggest that microplastic concentrations in coastal regions close to major sources reach values above 0.0001 g/m3 near the surface, dependent on the buoyancy of the plastic material and the amount of discharge. The comparison with observations shows that the model is able to reproduce the average concentrations of measured microplastics in the size class of 300 μm with statistical significance, but it underestimates the very high concentrations associated either with flooding or high river-runoff events or generated by sub-mesoscale transport. The model is able to reproduce the seasonal dynamic in Latvian and Estonian waters, except for October, when the increase of modelled microplastics in the ocean is too slow. But the general spatial patterns are sufficiently well reproduced, which makes the developed model a tool sufficient for the assessment of microplastic transport and accumulation pattern.

Regulation characteristics of underlying surface on runoff regime metrics and their spatial differences in typical urban communities across China - Yongyong Zhang; Jinjin Hou; Jun Xia; Dunxian She; Shengjun Wu; Xingyao Pan (Science China Earth Sciences, 2022)

Transport of Microplastics From the Daugava Estuary to the Open Sea - Vilnis Frishfelds; Jens Murawski; Jun She (Frontiers in Marine Science, 2022)
This study considers the transport of microplastics (MPs) from inland waters (rivers and lakes) to coastal waters and then to the open sea. A three-dimensional MP Eulerian tracer model based on the HIROMB-BOOS model (HBM) with wave-induced transport and biofouling process is used. Multilayer two-way nested model grids with 3–0.5–0.25–0.05 nautical mile resolutions are applied to resolve relevant riverine–estuarial–coastal hydrodynamics with a focus on the southern waters in the Gulf of Riga. The major river of the Gulf of Riga, Daugava, is governed by the Riga Hydro Power Station (RHPS) with high daily and weekly variability of the runoff creating more intense outflows during its working hours. This gives additional complexity when calibrating this model. The model results are validated against MP observations that are collected on various cruises in the summer of 2018 in the Gulf of Riga. There exists a strong synoptic variability in the observations, which are also reproduced. As the rivers are the primary source of MPs, a special backtracking algorithm was developed to find the most possible source of pollutants at a given location and time. The backtracking algorithm includes optimization with respect to salinity in order to prefer trajectories coming from freshwater and, consequently, MP sources. Lagrangian drift studies are performed for events with high precipitation in the estuary domain when sewer overflow at wastewater treatment plants (WWTPs) can occur, and the results are compared with different MP components in observations.

Uncertainty and Consistency Assessment in Multiple Microplastic Observation Datasets in the Baltic Sea - Jun She; Natalja Buhhalko; Kati Lind; Arun Mishra; Villu Kikas; Elisa Costa; Chiara Gambardella; Alessio Montarsolo; Marco Faimali; Francesca Garaventa; Inga Lips (Frontiers in Marine Science, 2022)
This paper aims to quantify data uncertainties in marine microplastic measurements, including spatiotemporal sampling error and sample volume estimation error, identify impacts of varying mesh sizes, sampling and analysis methods, and evaluate consistency in multiple microplastic observation datasets. Twenty-seven datasets on surface marine microplastics with particle size >100 µm in the Baltic Sea are compiled. Results show that the trawl datasets have a spatiotemporal sampling error of 25% for microlitter concentration, 36% for microplastic fiber concentrations and 40-56% for microplastic particle concentration. By taking surface currents and wave-induced Stokes drift into account, the sample volume of the trawl measurements is corrected, leading to a mean microplastic concentration correction of 12%. The differences of microplastic concentration between datasets with varying mesh sizes from 100 – 500 µm are not statistically significant. Analysis methods, however, can lead to significant differences in microplastic datasets. The dataset consistency is further examined among the three dataset categories using trawl, pump and bulk sampling techniques. It is found that an individual dataset is often self-consistent. Most of the datasets within one monitoring category are more consistent than those from different categories. More than 70% of the datasets within individual categories are consistent, which have mean microplastic concentration significantly smaller than the rest of the datasets. Significant inconsistencies are identified between different data categories. Six out of eight highest relative standard deviations are found in the pump and bulk datasets. The median value of the mean microplastic concentration from the 10 pump datasets is about 4.5 times as much as that of the 14 trawl datasets, both for fiber and non-fiber particles. Significant differences are also identified on microplastic fiber fraction in different dataset categories. Two thirds of the 13 bulk and pump datasets have a microplastic fiber fraction >85% while the 14 trawl datasets show much lower microplastic fiber fractions between 45-70%. In addition, the particle collection efficiency, potential leakage of particles with irregular shapes, clogging, the false zero samples and related lower limit of the detectable microplastic concentration for given sampling methods and water environment, are also discussed.

PM2.5-bound phthalates and phthalate substitutes in a megacity of southern China: spatioseasonal variations, source apportionment, and risk assessment - Yu-Qi Huang; Yuan Zeng; Tao Wang; She-Jun Chen; Yu-Feng Guan; Bi-Xian Mai (Environmental Science and Pollution Research, 2022)

Effectiveness of cascading time series models based on meteorological factors in improving health risk prediction - Shuopeng Jia; Weibin She; Zhipeng Pi; Buying Niu; Jinhua Zhang; Xihan Lin; Mingjun Xu; Weiya She; Jun Liao (Environmental Science and Pollution Research, 2022)

A new framework for the identification of flash drought: Multivariable and probabilistic statistic perspectives - Chen Hu; Jun Xia; Dunxian She; Lingcheng Li; Zhihong Song; Si Hong (International Journal of Climatology, 2021)
Flash drought is distinguished with seasonal drought by its characteristics of sudden onset and rapid intensification, and has attracted increasing concern due to the severe negative impacts on socioeconomic development and ecosystems. To accurate identify the onset time and propagation of flash drought is still a big challenge, as it is influenced by many factors (e.g., deficit in precipitation, increase in evapotranspiration and temperature, shortage in soil moisture, and etc.). This study aims to develop a probabilistic and multivariable flash drought identification method (PMFDI) from the perspective of considering the interaction effects from different driving factors on flash drought occurrence and propagation with a multivariable statistical tool. The PMFDI uses the weekly standardized precipitation evapotranspiration index and the standardized soil moisture index to describe the abnormally changes in multiple hydrometeorological variables over a short duration. The linearly multivariable index (LMI) is employed to describe the correlation relationship between multiple hydrometeorological variables and to identify flash droughts from the aspects of sudden onset and rapid intensification. We select the Loess Plateau (LP) in China to verify the efficiency of the developed PMFDI with the comparison to the other two recently proposed flash drought identification methods. The results indicate that PMFDI can identify high‐ and low‐ frequency regions similar to those identified by the other two methods and can generally recognize actual flash droughts. In addition, the PMFDI can capture the comprehensive impact of multiple hydrometeorological variables as well as their interaction on flash drought occurrence, which provides a useful perspective to understand the propagation processes of the actual flash droughts in the LP.

A Cross Disciplinary Framework for Cost-Benefit Optimization of Marine Litter Cleanup at Regional Scale - Asbjørn Christensen; Kostas Tsiaras; Jens Murawski; Yannis Hatzonikolakis; Jun She; Michael St. John; Urmas Lips; Roy Brouwer (Frontiers in Marine Science, 2021)
Litter cleanup and disposal management in the marine environment are increasingly subject to public scrutiny, government regulation and stakeholder initiatives. In practice, ongoing efforts and new investment decisions, for example in new cleanup technologies, are constrained by financial and economic resources. Given budgetary restrictions, it is important to optimize decision-making using a scientific framework that takes into account the various effects of investments by combining multiple scientific perspectives and integrating these in a consistent and coherent way. Identifying optimal levels of marine litter cleanup is a challenge, because of its cross-disciplinary nature, involving physics, environmental engineering, science, and economics. In this paper, we propose a bridge-building, spatial cost-benefit optimization framework that allows prioritizing where to apply limited cleanup efforts within a regional spatial network of marine litter sources, using input from the maturing field of marine litter transport modeling. The framework also includes ecosystem functioning in relation to variable litter concentrations, as well as the potentially non-linear cost-efficiency of cleanup technologies. From these three components (transport modeling, ecosystem functioning, cleanup-effectiveness), along with litter source mapping, we outline the optimal cleanup solution at any given ecological target or economic constraint, as well as determine the cleanup feasibility. We illustrate our framework in a Baltic and Mediterranean Sea case study, using real data for litter transport and cleanup technology. Our study shows that including pollution Green's functions is essential to assess the feasibility of cleanup and determine optimal deployment of cleanup investments, where the presented framework combines physical, economical, technological and biological data consistently to compare and rank alternatives.

Effect of Three Gorges Dam on Poyang Lake water level at daily scale based on machine learning - Sheng Huang; Jun Xia; Sidong Zeng; Yueling Wang; Dunxian She (Journal of Geographical Sciences, 2021)

Ocean Circulation Model Applications for the Estuary-Coastal-Open Sea Continuum - Jens Murawski; Jun She; Christian Mohn; Vilnis Frishfelds; Jacob Woge Nielsen (Frontiers in Marine Science, 2021)
Coastal zones are among the most variable environments. As such, they require adaptive water management to ensure the balance of economic and social interests with environmental concerns. High quality marine data of hydrographic conditions e.g., sea level, temperature, salinity, and currents are needed to provide a sound foundation for the decision making process. Operational models with sufficiently high forecasting quality and resolution can be used for a further extension of the marine service toward the coastal-estuary areas. The Limfjord is a large and shallow water body in Northern Jutland, connecting the North Sea in the West and the Kattegat in the East. It is currently not covered by the CMEMS service, despite its importance for sea shipping, aquaculture and mussel fisheries. In this study, we use the operational HIROMB-BOOS Model (HBM) to resolve the full Baltic-Limfjord-North Sea system with a horizontal resolution of 185.2 m in the Limfjord. The study shows several factors that are essential for successfully modeling the coastal-estuary system: (a) high computational efficiency and flexible grids to allow high resolution in the fjord, (b) an improved short wave radiation scheme to model the thermodynamics and the diurnal variability of the temperature in very shallow waters, (c) high resolution atmospheric forcing, (d) adequate river forcing, and (e) accurate bathymetry in the narrow straits. With properly resolving these issues, the system is able to provide high quality sea level forecast for storm surge warning and hydrography forecasts: temperature, salinity and currents with sufficiently good quality for ecosystem-based management. The model is able to simulate the complex spatial and temporal pattern of sea level, salinity and temperature in the Limfjord and to reproduce their diurnal, seasonal and interannual variability and stratification rather well. Its high computational efficiency makes it possible to model the transition from the basin-scales to coastal- and estuary-scales seamlessly. In total, The HBM model has been successfully extended, to include the complex estuary system of the Limfjord, and shows an adequate model performance with regards to sea level, salinity and temperature predictions, suitable for storm surge warning applications and coastal management applications.

miR-23a-3p regulated by LncRNA SNHG5 suppresses the chondrogenic differentiation of human adipose-derived stem cells via targeting SOX6/SOX5 - Zhen Yang; Zhijing Ren; Rongfeng She; Jun Ao; Qingde Wa; Zeyu Sun; Bo Li; Xiaobin Tian (Cell and Tissue Research, 2021)

Naringin Targets NFKB1 to Alleviate Oxygen-Glucose Deprivation/Reoxygenation–Induced Injury in PC12 Cells Via Modulating HIF-1α/AKT/mTOR-Signaling Pathway - Wei Cao; She-Jun Feng; Min-Chen Kan (Journal of Molecular Neuroscience, 2021)

Effects of Enzymatic Hydrolysate of Oyster on Erectile Function in Male Hemicastrated Rats - Hai-Yan Wang; Zheng Yan; Shuang Liu; Ai-Qing Liu; Jun-She Sun (International Journal of Peptide Research and Therapeutics, 2020)

l-Glutamic acid induced the colonization of high-efficiency nitrogen-fixing strain Ac63 (Azotobacter chroococcum) in roots of Amaranthus tricolor - Yi-Fan Wang; Jun-Feng Wang; Zhi-Min Xu; Shao-Hua She; Jun-Qing Yang; Qu-Sheng Li (Plant and Soil, 2020)

Operational Modeling Capacity in European Seas—An EuroGOOS Perspective and Recommendations for Improvement - Arthur Capet; Vicente Fernández; Jun She; Tomasz Dabrowski; Georg Umgiesser; Joanna Staneva; Lőrinc Mészáros; Francisco Campuzano; Laura Ursella; Glenn Nolan; Ghada El Serafy (Frontiers in Marine Science, 2020)

The European Marine Observation and Data Network (EMODnet): Visions and Roles of the Gateway to Marine Data in Europe - Belén Martín Míguez; Antonio Novellino; Matteo Vinci; Simon Claus; Jan-Bart Calewaert; Henry Vallius; Thierry Schmitt; Alessandro Pititto; Alessandra Giorgetti; Natalie Askew; Sissy Iona; Dick Schaap; et al. (Frontiers in Marine Science, 2019)

An Integrated Approach to Coastal and Biological Observations - Jun She; Ángel Muñiz Piniella; Lisandro Benedetti-Cecchi; Lars Boehme; Ferdinando Boero; Asbjorn Christensen; Tasman Crowe; Miroslaw Darecki; Enrique Nogueira; Antoine Gremare; Francisco Hernandez; Tarmo Kouts; et al. (Frontiers in Marine Science, 2019)

From Observation to Information and Users: The Copernicus Marine Service Perspective - Pierre Yves Le Traon; Antonio Reppucci; Enrique Alvarez Fanjul; Lotfi Aouf; Arno Behrens; Maria Belmonte; Abderrahim Bentamy; Laurent Bertino; Vittorio Ernesto Brando; Matilde Brandt Kreiner; Mounir Benkiran; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Spatiotemporal variation and statistical characteristic of extreme precipitation in the middle reaches of the Yellow River Basin during 1960–2013 - Yin Zhang; Jun Xia; Dunxian She (Theoretical and Applied Climatology, 2019)

Proteomic discovery of H2O2 response in roots and functional characterization of PutGLP gene from alkaligrass - Juanjuan Yu; Yongxue Zhang; Junming Liu; Lin Wang; Panpan Liu; Zepeng Yin; Siyi Guo; Jun Ma; Zhuang Lu; Tai Wang; Yimin She; Yuchen Miao; et al. (Planta, 2018)

Assessing the influence of climate change and inter-basin water diversion on Haihe River basin, eastern China: a coupled model approach - Jun Xia; Qiang Wang; Xiang Zhang; Rui Wang; Dunxian She (Hydrogeology Journal, 2018)

Characteristics of dry-wet abrupt alternation events in the middle and lower reaches of the Yangtze River Basin and the relationship with ENSO - Lijie Shan; Liping Zhang; Jiyun Song; Yanjun Zhang; Dunxian She; Jun Xia (Journal of Geographical Sciences, 2018)

Analysis of Impacts of Climate Change and Human Activities on Hydrological Drought: a Case Study in the Wei River Basin, China - Lei Zou; Jun Xia; Dunxian She (Water Resources Management, 2018)

Copulas-Based Drought Characteristics Analysis and Risk Assessment across the Loess Plateau of China - Dunxian She; Jun Xia (Water Resources Management, 2018)

Molecular docking, binding free energy analysis, and biological evaluation of bisabolonalone hydrazone carboxamides as H+,K+-ATPase reversible inhibitors - Xin-Xin She; Qing Dong; Hua-Jun Luo; Jun-Zhi Wang; Nian-Yu Huang; Wei-Qiao Deng; Kun Zou (Medicinal Chemistry Research, 2018)

Comparisons of Evaluation Factors and Application Effects of the New [BQ]GSI System with International Rock Mass Classification Systems - Shen Yan-jun; Yan Rui-xin; Yang Geng-she; Xu Guang-li; Wang Shan-yong (Geotechnical and Geological Engineering, 2017)

Numerical simulation of a high-speed landslide in Chenjiaba, Beichuan, China - Tao Huang; Ming-tao Ding; Tao She; Shu-jun Tian; Jiang-tao Yang (Journal of Mountain Science, 2017)

Male-Produced Aggregation Pheromone of Coffee Bean Weevil, Araecerus fasciculatus - Shuai Yang; Xiao-Fang Zhang; Yu-Lin Gao; Dan Chen; Dong-Mei She; Tao Zhang; Jun Ning (Journal of Chemical Ecology, 2017)

Attraction of Coffee Bean Weevil, Araecerus fasciculatus, to Volatiles from the Industrial Yeast Kluyveromyces lactis - Shuai Yang; Xiang-Dong Mei; Xiao-Fang Zhang; Yao-Fa Li; Dongmei She; Tao Zhang; Jun Ning (Journal of Chemical Ecology, 2017)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Developing European operational oceanography for Blue Growth, climate change adaptation and mitigation, and ecosystem-based management - Jun She; Icarus Allen; Erik Buch; Alessandro Crise; Johnny A. Johannessen; Pierre-Yves Le Traon; Urmas Lips; Glenn Nolan; Nadia Pinardi; Jan H. Reißmann; John Siddorn; Emil Stanev; et al. (Ocean Science, 2016)
Operational approaches have been more and more widely developed and used for providing marine data and information services for different socio-economic sectors of the Blue Growth and to advance knowledge about the marine environment. The objective of operational oceanographic research is to develop and improve the efficiency, timeliness, robustness and product quality of this approach. This white paper aims to address key scientific challenges and research priorities for the development of operational oceanography in Europe for the next 5–10 years. Knowledge gaps and deficiencies are identified in relation to common scientific challenges in four EuroGOOS knowledge areas: European Ocean Observations, Modelling and Forecasting Technology, Coastal Operational Oceanography and Operational Ecology. The areas “European Ocean Observations” and “Modelling and Forecasting Technology” focus on the further advancement of the basic instruments and capacities for European operational oceanography, while “Coastal Operational Oceanography” and “Operational Ecology” aim at developing new operational approaches for the corresponding knowledge areas.

Changes of rainfall and its possible reasons in the Nansi Lake Basin, China - Dunxian She; Jun Xia; Longteng Zhu; Junmei Lü; Xiangdong Chen; Liping Zhang; Xiang Zhang (Stochastic Environmental Research and Risk Assessment, 2016)

Isolation and characterization of a crude oil degrading bacteria from formation water: comparative genomic analysis of environmental Ochrobactrum intermedium isolate versus clinical strains - Lu-jun Chai; Xia-wei Jiang; Fan Zhang; Bei-wen Zheng; Fu-chang Shu; Zheng-liang Wang; Qing-feng Cui; Han-ping Dong; Zhong-zhi Zhang; Du-jie Hou; Yue-hui She (Journal of Zhejiang University-SCIENCE B, 2015)

Direct cloning, expression of a thermostable xylanase gene from the metagenomic DNA of cow dung compost and enzymatic production of xylooligosaccharides from corncob - Ming-zhe Sun; Hong-chen Zheng; Ling-cai Meng; Jun-she Sun; Hui Song; Yun-juan Bao; Hai-sheng Pei; Zheng Yan; Xiu-qing Zhang; Jing-sheng Zhang; Yi-han Liu; Fu-ping Lu (Biotechnology Letters, 2015)

Spatial distribution and temporal trends of mercury and arsenic in remote timberline coniferous forests, eastern of the Tibet Plateau, China - Ronggui Tang; Haiming Wang; Ji Luo; Shouqin Sun; Yiwen Gong; Jia She; Youchao Chen; Yang Dandan; Jun Zhou (Environmental Science and Pollution Research, 2015)

Nitrogen and phosphorus loss and optimal drainage time of paddy field under controlled drainage condition - Meng-hua Xiao; Shuang-en Yu; Dongli She; Xiu-jun Hu; Lin-lin Chu (Arabian Journal of Geosciences, 2015)

Occurrence, sources, and ecological risks of PBDEs, PCBs, OCPs, and PAHs in surface sediments of the Yangtze River Delta city cluster, China - Ting Zhang; Wen-Long Yang; She-Jun Chen; Dian-Long Shi; Hu Zhao; Yi Ding; Ye-Ru Huang; Nan Li; Yue Ren; Bi-Xian Mai (Environmental Monitoring and Assessment, 2014)

Spatio-temporal variation and statistical characteristic of extreme dry spell in Yellow River Basin, China - Dunxian She; Jun Xia; Jiyun Song; Hong Du; Junxu Chen; Long Wan (Theoretical and Applied Climatology, 2013)

The spatial and temporal analysis of dry spells in the Yellow River basin, China - Dunxian She; Jun Xia (Stochastic Environmental Research and Risk Assessment, 2013)

Lentivirus-mediated Sirt1 shRNA and resveratrol independently induce porcine preadipocyte apoptosis by canonical apoptotic pathway - Wei-Jun Pang; Yan Xiong; Zhao Zhang; Ning Wei; Ni Chen; Gong-she Yang (Molecular Biology Reports, 2013)

A Combination Method to Study the Effects of Petroleum on Soil Microbial Activity - Wen Wen She; Jun Yao; Fei Wang; Min Min Cai; Jing Wei Wang; Chang Shun Song (Bulletin of Environmental Contamination and Toxicology, 2013)

Temporal and spatial variations and statistical models of extreme runoff in Huaihe River Basin during 1956–2010 - Jun Xia; Hong Du; Sidong Zeng; Dunxian She; Yongyong Zhang; Ziqi Yan; Yan Ye (Journal of Geographical Sciences, 2012)

Regression analysis between environmental factors and earthquake-damaged trace: a case study in Wenchuan County, China - Yong Luo; Hui Yu; Zhi-Jun Zheng; Tao She (International Journal of Remote Sensing, 2012)

Spatio-temporal trend and statistical distribution of extreme precipitation events in Huaihe River Basin during 1960–2009 - Jun Xia; Dunxian She; Yongyong Zhang; Hong Du (Journal of Geographical Sciences, 2012)

Heavy Metals in Hair of Residents in an E-Waste Recycling Area, South China: Contents and Assessment of Bodily State - Jing Zheng; Xiao-Jun Luo; Jian-Gang Yuan; Luo-Yiyi He; Yi-Hui Zhou; Yong Luo; She-Jun Chen; Bi-Xian Mai; Zhong-Yi Yang (Archives of Environmental Contamination and Toxicology, 2011)

Polychlorinated biphenyls and organochlorinated pesticides in birds from a contaminated region in South China: association with trophic level, tissue distribution and risk assessment - Xiu-Lan Zhang; Xiao-Jun Luo; Juan Liu; Yong Luo; She-Jun Chen; Bi-Xian Mai (Environmental Science and Pollution Research, 2011)

Screening Level of PAHs in Sediment Core from Lake Hongfeng, Southwest China - Jian-Yang Guo; Feng-Chang Wu; Liang Zhang; Hai-Qing Liao; Run-Yu Zhang; Wei Li; Xiao-Li Zhao; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2011)

Polybrominated Diphenyl Ethers (PBDEs), Polychlorinated Biphenyles (PCBs), Hydroxylated and Methoxylated-PBDEs, and Methylsulfonyl-PCBs in Bird Serum from South China - Juan Liu; Xiao-Jun Luo; Le-Huan Yu; Ming-Jing He; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2010)

Experimental determination of calcite dissolution rates and equilibrium concentrations in deionized water approaching calcite equilibrium - Qingjie Gong; Jun Deng; Qingfei Wang; Liqiang Yang; Min She (Journal of Earth Science, 2010)

Increasing polybrominated diphenyl ether (PBDE) contamination in sediment cores from the inner Clyde Estuary, UK - Christopher H. Vane; Yun-Juan Ma; She-Jun Chen; Bi-Xian Mai (Environmental Geochemistry and Health, 2010)

Tissue expression of porcine FoxO1 and its negative regulation during primary preadipocyte differentiation - Wei-Jun Pang; Tai-Yong Yu; Liang Bai; Yan-Jun Yang; Gong-She Yang (Molecular Biology Reports, 2009)

Distribution and partition of polycyclic aromatic hydrocarbon in surface water of the Pearl River Estuary, South China - Xiao-Jun Luo; Bi-Xian Mai; Qing-Shu Yang; She-Jun Chen; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

Assessment of sampling designs to measure riverine fluxes from the Pearl River Delta, China to the South China Sea - Hong-Gang Ni; Feng-Hui Lu; Xian-Lin Luo; Hui-Yu Tian; Ji-Zhong Wang; Yu-Feng Guan; She-Jun Chen; Xiao-Jun Luo; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

Distribution, Source Apportionment, and Transport of PAHs in Sediments from the Pearl River Delta and the Northern South China Sea - Xiao-Jun Luo; She-Jun Chen; Bi-Xian Mai; Guo-Ying Sheng; Jia-Mo Fu; Eddy Y. Zeng (Archives of Environmental Contamination and Toxicology, 2008)

Modulation of Sirt1 by resveratrol and nicotinamide alters proliferation and differentiation of pig preadipocytes - Liang Bai; Wei-Jun Pang; Yan-Jun Yang; Gong-She Yang (Molecular and Cellular Biochemistry, 2007)

Regulation of metabolite production by precursors and elicitors in liquid cultures of Hypericum perforatum - Xiao-Na Liu; Xiu-Qing Zhang; Shi-Xiang Zhang; Jun-She Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Reflection and Transmission of Elastic Waves from the Interface of a Fluid-saturated Porous Solid and a Double Porosity Solid - Zhi-Jun Dai; Zhen-Bang Kuang; She-Xu Zhao (Transport in Porous Media, 2006)

Different effects of p58PITSLRE on the apoptosis induced by etoposide, cycloheximide and serum-withdrawal in human hepatocarcinoma cells - Ming M. Cai; Song W. Zhang; Si Zhang; She Chen; Jun Yan; Xiao Y. Zhu; Yun Hu; Chun Chen; Jian X. Gu (Molecular and Cellular Biochemistry, 2002)